Occupational decision motives of potential TVET teachers: New standards of pre-service TVET teachers’ recruitment and career development - Eze, Nicholas; Nwadi, Calister; Onodugo, Ifeoma; Ozioko, Ekene; Osondu, Stella; Nwosu, Ogochukwu; Chilaka, Akuchinyere; Obichukwu, Uzochukwu; Anorue, Honesta; Onyishi, Ifeyinwa; Eze, Emmanuel; Onyemachi, Chidinma; et al. (Frontiers in Education, 2022)
This study investigated the underlying factors that influences pre-service Nigerian (TVET) teachers' decision to pursue a teaching career which aids in recruiting more teachers. Preservice TVET teachers are the teachers who are being prepared to teach in a vocation requiring technical skills. The motivation of these pre-service TVET teachers obtaining a postgraduate diploma in technical education was investigated using the quantitative research design approach to collect data via a researcher-created, self-administered questionnaire. Participants were selected from two cohorts (N=78) of students enrolled in the various departments for the Postgraduate Diploma in Technical Education (PGDTE) program of the University of Nigeria. According to the quantitative analysis, excellent role models from previous teachers, the demanding nature of the job role, a willingness to impart relevant knowledge and skills, a willingness to assist financially disadvantaged students in gaining marketable job skills, and the country's presumed demand for TVET teachers were the primary motivators for pre-service teachers. However, the gender aspect revealed that male and female pre-service TVET teachers showed significant differences in their altruistic and intrinsic impulses when the non-parametric Mann-Whitney U Tests were utilized to analyze extracted data on gender. The ramifications of the findings were then examined, as well as their significance in enhancing hiring measures through setting of standards for technical and vocational education programs in the universities to improve on the status of pre-service TVET teachers to attract quality graduates of technical education programs who can teach as TVET teachers before and after completing their programs.